DARI MUKJIZAT KE KEMISKINAN ABSOLUT: PERLAWANAN PETANI DI RIAU MASA ORDE BARU DAN REFORMASI 1970-2010 (History Department, Semarang State University and Historian Society of Indonesia, 2017)
The research objective is to learn the unjustice economic policy. It is necessary look for alternative policies that favor the farmers. The research method was qualitative. The method was carried out through a series of interviews with resource persons who understand the problem. In addition, documentary method was used. The research found that the life of the poor peasants are deeply deprived. Their land, field, forest and jungle had been grabbed by the state and the capitalist. After being land grabbed, they serve as slaves and receive small wages which were only sufficient to survive. During the dry season, these slaves were told to burn the land. If caught, the charge falls on them.